32.9k views
4 votes
For f(x)=1/x^2-3

Find
A) f(3)
B) f(2-h)

Please show/explain how if you can .

For the function defined by the following attachment, evaluate f(0)

For f(x)=1/x^2-3 Find A) f(3) B) f(2-h) Please show/explain how if you can . For the-example-1
User Yanshof
by
6.1k points

1 Answer

4 votes

For f(x)=1/x^2-3

Find

A) f(3)

B) f(2-h)

If f(x)=1/x^2-3, then f(3) = 1 / 3^2 - 3. The exponentiation here must be carried out first: f(3) = 1/9 - 3. Then f(3) = 1/9 - 27/9 = -26/9

If f(x)=1/x^2-3, then f(2-h) = 1 / [2-h]^2 - 3. This result may be left as is or expanded. In expanded form, we have:

1

f(2-h) = ------------------ - 3

4-4h +h^2

User FatalKeystroke
by
6.8k points